Analisis Dampak Ekonomi Wisata Hiu Paus Terhadap Pendapatan Masyarakat Batubarani Gorontalo - Wolok, Eduart (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
This study aims to determine the economic impact of Whale Sharks travel to revenue of  Batubarani villagers in Gorontalo . This study was conducted in January-May 2016. Datacollection was done by direct observation using questionnaires . The economic impact wasanalyzed by using Keynesian Income Multiplier . The results showed that the impact of whalesharks travel to people's income Batubarani at the high category . Income Keynesian Multipliervalue is 1:52 , Type 1 Income Multiplier Ratio is 1.61 and Type 2 Income Multiplier Ratio is1.97.